2015
DOI: 10.1186/s12940-015-0047-2
|View full text |Cite
|
Sign up to set email alerts
|

Within- and between-group regression for improving the robustness of causal claims in cross-sectional analysis

Abstract: BackgroundA major objective of environmental epidemiology is to elucidate exposure-health outcome associations. To increase the variance of observed exposure concentrations, researchers recruit individuals from different geographic areas. The common analytical approach uses multilevel analysis to estimate individual-level associations adjusted for individual and area covariates. However, in cross-sectional data this approach does not differentiate between residual confounding at the individual level and at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…By including both β W and β B in the same model, the individual estimates are adjusted for, and independent of, the effect of the other estimate. The random effect term , which estimates the difference between each group intercept γ j and the overall intercept α 0 , accounts for the residual structure in the data corresponding to all unaccounted familial factors (both genetic and environmental) that contribute to the trait similarity of the twins 54,55 .…”
Section: Discussionmentioning
confidence: 99%
“…By including both β W and β B in the same model, the individual estimates are adjusted for, and independent of, the effect of the other estimate. The random effect term , which estimates the difference between each group intercept γ j and the overall intercept α 0 , accounts for the residual structure in the data corresponding to all unaccounted familial factors (both genetic and environmental) that contribute to the trait similarity of the twins 54,55 .…”
Section: Discussionmentioning
confidence: 99%
“…The random effect term , which estimates the difference between each group intercept and the overall intercept , accounts for the residual structure in the data corresponding to all unaccounted familial factors (both genetic and environmental) that contribute to the trait similarity of the twins. 61 , 62 …”
Section: Methodsmentioning
confidence: 99%
“…The ICC is the ratio of the between-family (i.e., random intercept) variance over the total variance and is an estimate of how much of the total variation in the outcome is accounted for by family: where is the covariance between the family variable, in this case family ID, and the outcome, and indicates the residual variance capturing within-twin pair differences. The total effect of the relationship between GPS and outcome is the ICC weighted sum of the within- and between-family effects: 62 It follows from Equation 3 that the total effect ranges between and . If the relationship between GPS and outcome is mostly due to individual-level variation, the ICC approximates 0 and the total effect will be close to .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study to specifically examine the relation of PFAS with CHD in adults with diabetes. Although PFAS have been linked to a number of adverse health outcomes, including dyslipidemia,(2, 3) these compounds have also been inversely associated with other cardiovascular disease risk factors such as CRP (25) and kidney function. (17) In the current study, PFAS showed a significant, inverse relationship with CHD; this association persisted after controlling for kidney function and other potentially confounding factors, and remained after stratification by chronic kidney disease status.…”
Section: Discussionmentioning
confidence: 99%